The Relationship Between the Sociology of Law and Social Change in Society (The Phenomenon of Guiding Children Through a Military Approach) - Mauludin Malik, Sonang (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
In general, every society on earth will experience what is known as change. This change can be recognized and felt when we make a comparison by examining the state of society at a certain time and then comparing it with the state of society in the past. Law plays an active role as something that can determine human behavior that deviates from the rule of law. For law to be effective and responsive, it must be formed from the realities of life in society. This is in line with the function of law as a means of renewal in society, namely to direct society towards a better direction so as to create order in society. Law can be a means of renewal for society if it is accepted by society, and the law accepted by society is certainly law that arises from the needs of society. In this research, the method used is a descriptive research method whose function is to describe ongoing phenomena as well as describe phenomena in the past. Sociology of Law as a branch of legal science is useful for photographing phenomena that occur in society, providing the ability to understand law in a social context, mastery of the concepts of sociology of law can provide the ability to conduct analysis of the effectiveness of law in society, both as a means of social control, a means to change society and a means to regulate social interaction, in order to achieve certain social conditions, and sociology of law provides possibilities and the ability to conduct evaluations of the effectiveness of law in society.